Desarrollo de un plan de mantenimiento para las líneas de producción de la procesadora de Lácteos Los Ángeles S.A.S (2018)
To carry out the planned maintenance plan began with the creation of a format for data collection during the first 3 months; so from the beginning, data was collected for the entire development of the project. Parallel to this activity, began to describe the company in all its functions, operation and machinery, which were going to intervene, observing the state of maintenance. A process for coding the equipment was established and a criticality system was applied to determine to which teams to apply the plan. Technical sheets, resume formats, work orders and a database for all teams were prepared. Activities and frequencies were carried out for critical teams, the results were evaluated, and management indicators were calculated. Spare parts analysis and supplier evaluation were done. The improvement recommendations and a financial evaluation that shows the viability of the project were raised.